Impact of social media advertising on consumer buying behaviour among millennial women / Nur Iman Mohd Suharman - Mohd Suharman, Nur Iman (Faculty of Business and Management, 2020)
In the new era of the advertising industry, social media advertising is undergoing rapid and extraordinary changes. Commonly, social media advertising is a communication platform that is exercised to inform, persuade and remind consumers about the existence of certain products or services. Moreover, social media advertising too has become on of the online marketing techniques to encourage or captivating audiences into purchasing products and services. Besides that, in Malaysia, women shop online more than men and Millennials havea stronger interest in social media as they are comfortable with the usage of interactive technologies to source entertainment. Thus, the main purpose of the study is to identify the impact of social media advertising on consumer buying behaviour among Millennial women. The independent variables of this research are Quality of Product Advertised, Price of Product Advertised, Brand Image and Social Media Influencers. On top of that, this study was conducted towards Millennial Women in Malaysia. A total of 200 questionnaires were distributed and analysed. Moreover, the data was measured by using Statistical Package for Social Science Program (SPSS) software version 25.0, to showcase the most influential variables of social media advertising on consumer buying behaviour. The findings in this study shows that, Quality of Product Advertised and Brand Image are the most influential characteristics of social media advertising on consumer buying behaviour. Lastly, the discussion of the findings and suggestions for future research are identified and proposed in the last chapter of this study.